Mechanisms of the Development of Cardiotoxicity in Breast Cancer Chemirterapy (Eurasian Research Bulletin, 2023)
Modern treatment of breast cancer is associated with risks of cardiotoxicity. The article presents the mechanisms of cardiotoxicity development on the example of drugs used in the treatment of breast cancer (anthracyclines and a targeted drug - trastuzumab). Diagnostic methods, their advantages and disadvantages, the algorithm of diagnosis and continuation of therapy of patients receiving cardiotoxic therapy of breast cancer are presented.